Paving the way for better ototoxicity assessments in cisplatin therapy using more reliable animal models - Manickam, Vijayprakash; Zallocchi, Marisa (Frontiers in Cellular Neuroscience, 2025)
Cisplatin-induced hearing loss is a common and irreversible side effect affecting a significant proportion of cancer patients. While various strategies to mitigate this toxicity have been explored, there remains a critical need for effective treatments. A major challenge in developing new therapies is the lack of reliable animal models that accurately replicate the clinical use of cisplatin in humans, which typically involves multiple cycles of low-dose administration. Traditional models using high doses of cisplatin have resulted in high mortality and variable hearing loss, complicating the assessment of potential treatments. To address this, a multi-cycle model using lower cisplatin doses in mice was developed, providing hearing loss without mortality. However, variability in outcomes across different research groups persisted. In the present study, we optimize the multi-cycle model of cisplatin-induced ototoxicity by using clinical-grade cisplatin rather than laboratory-grade formulations. The use of clinical cisplatin ensures greater consistency, reliability, and relevance to human treatment protocols, as it adheres to the rigorous quality standards required for patient use. This new administration protocol will minimize variability across research laboratories and more accurately mimic the dosing regimens typically administered to cancer patients. Additionally, we have enhanced a zebrafish model for high-throughput screening of potential therapeutics, further improving the consistency of results. These improvements to the animal models are critical for accelerating the discovery and testing of therapies to prevent cisplatin-induced hearing loss, supporting the development of effective treatments for cancer patients undergoing cisplatin chemotherapy.